2018
DOI: 10.1016/j.apmr.2017.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Spastic Stretch Reflexes at the Elbow by Flexion Synergy Expression in Individuals With Chronic Hemiparetic Stroke

Abstract: Because flexion synergy expression modifies stretch reflexes in involved muscles, interventions that reduce flexion synergy expression may confer the added benefit of reducing spasticity during functional use of the arm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 45 publications
0
45
1
Order By: Relevance
“…However, some signs of an increased neuromodulatory influence appear to diminish when muscles are volitionally preactivated. For example, we and others have demonstrated that stretch reflex amplitude equilibrates between paretic and non-paretic muscles when the muscles are preactivated to the same extent prior to stretch (Lee et al, 1987 ; Burne et al, 2005 ; Mottram et al, 2009 , 2010 ; McPherson et al, 2017 ). Additionally, some estimates of PIC amplitude are indistinguishable between paretic and control muscles during volitional ramp contractions (Mottram et al, 2009 , 2010 ).…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…However, some signs of an increased neuromodulatory influence appear to diminish when muscles are volitionally preactivated. For example, we and others have demonstrated that stretch reflex amplitude equilibrates between paretic and non-paretic muscles when the muscles are preactivated to the same extent prior to stretch (Lee et al, 1987 ; Burne et al, 2005 ; Mottram et al, 2009 , 2010 ; McPherson et al, 2017 ). Additionally, some estimates of PIC amplitude are indistinguishable between paretic and control muscles during volitional ramp contractions (Mottram et al, 2009 , 2010 ).…”
Section: Introductionmentioning
confidence: 87%
“…Focal ischemic stroke causes changes in descending neural drive that alter spinal motor excitability (Stinear et al, 2007 ; Heckman et al, 2009 ; Bradnam et al, 2012 ; McMorland et al, 2015 ; McPherson et al, 2017 , 2018 ; Owen et al, 2017 ). This can occur through direct effects on spinal neurons and/or by facilitating adaptive processes associated with shifts in the overall balance of spinal excitation and inhibition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Building on recent work (Condliffe et al 2005; McPherson et al 2011; McPherson et al 2017), we chose to use larger displacement stretches (~90 degrees) than are traditionally used with ramp-and-hold (Powers et al 1989; Powers et al 1988; Thilmann et al 1991), pseudo-random binary (Ludvig et al 2011; Mirbagheri et al 2012), or multi-sine perturbations (Forbes et al 2011; Ludvig et al 2011; Mirbagheri et al 2012). The choice of large displacement ramp-and-hold stretches facilitates clinical translation because it most closely mirrors current clinical examinations in terms of the stretch profile (e.g., Ashworth, Tardieu), it does not require reprogramming of commercially available mechatronic devices, it does not require use of advanced system identification techniques or applied mathematics to compute reflex-related parameters (as do pseudo-random binary and multisine perturbations), and it ensures a sufficient angular range over which to exceed the threshold angle and estimate reflex stiffness.…”
Section: Methodsmentioning
confidence: 99%
“…The contralesional elbow flexors are implicated in a variety of functional impairments arising from changes in spinal motor excitability, including flexion synergy expression and spasticity (Ellis et al 2017; Jin and Zhao 2018; McPherson et al 2018a; McPherson et al 2018b; Sommerfeld et al 2012). We balance the competing needs of efficient implementation and high precision by using a clinically available mechatronic device and biomechanical measures of the stretch reflex response.…”
Section: Introductionmentioning
confidence: 99%